2022
DOI: 10.3389/fphy.2022.888832
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Coherent Turbulent Structures via Deep Learning

Abstract: Turbulent flow is widespread in many applications, such as airplane wings or turbine blades. Such flow is highly chaotic and impossible to predict far into the future. Some regions exhibit a coherent physical behavior in turbulent flow, satisfying specific properties; these regions are denoted as coherent structures. This work considers structures connected with the Reynolds stresses, which are essential quantities for modeling and understanding turbulent flows. Deep-learning techniques have recently had promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…A U-net architecture 24 is used for predicting the velocity field. This architecture efficiently exploits spatial correlations in the data, and further develops the work by Schmekel et al 30 . Note that U-nets and other computer-vision architectures have been successfully used in the context of turbulent-flow predictions 28,[64][65][66][67] .…”
Section: Deep-neural-network Architecture and Predictionmentioning
confidence: 89%
See 1 more Smart Citation
“…A U-net architecture 24 is used for predicting the velocity field. This architecture efficiently exploits spatial correlations in the data, and further develops the work by Schmekel et al 30 . Note that U-nets and other computer-vision architectures have been successfully used in the context of turbulent-flow predictions 28,[64][65][66][67] .…”
Section: Deep-neural-network Architecture and Predictionmentioning
confidence: 89%
“…To accomplish this objective, we will first show how U-nets can predict the evolution of turbulent channel flow, extending our earlier work 30 . We start with a database of 6000 instantaneous realizations obtained from turbulent channel flow simulations, see the “Methods” section for additional details on the data generation.…”
Section: Introductionmentioning
confidence: 93%
“…A convolutional neural network (CNN) is used for predicting the velocity field, as discussed by Schmekel et al [30]. Note that CNNs and other computer-vision architectures have been successfully used in the context of turbulent-flow predictions [28,[58][59][60][61].…”
Section: Deep-neural-network Architecture and Predictionmentioning
confidence: 99%
“…The network employed in this work consists of 4 layers of 3D CNN blocks, which contain plain convolutional and residual blocks [62]. The architecture, similar to the one used by Schmekel et al [30], is shown in epochs, where all training data is used once in a single epoch.…”
Section: Deep-neural-network Architecture and Predictionmentioning
confidence: 99%
See 1 more Smart Citation